13-Hour progression of emphysematous hepatitis as depicted on repeat computerized tomography. Issue 4 (30th April 2020) - Calderon, Holly; Serfin, Jennifer
Abstract: Emphysematous hepatitis is a rare, rapidly progressive and often fatal condition, which occurs predominantly in patients with uncontrolled diabetes mellitus. It results in the replacement of liver parenchyma by a collection of gas. Emphysematous infections of other abdominal and pelvic organs have long been established, but relatively little is known about the equivalent emphysematous infection of the liver with very few examples in the published literature. A review of the literature shows variability regarding timing of presentation and implicated organisms. To date, computerized tomography imaging has been purported to be diagnostic and vital to early management, as it clearly shows the characteristic appearance of air bubbles within the liver parenchyma. We report a case with inconclusive initial radiographic findings.